Response of Growth and Production of Corn (Zea Mays L) with Liquid Fertilizer in Labuhan Batu Regency - Fitra Syawal Harahap Harahap; Hilwa Walida; Dahrul Aman Harahap; Roswita Oesman; Wizni Fadhillah (Talenta Publisher, 2019)
Growth and Production of Corn Plants (Zea mays L) with Provision of liquid supplementary fertilizer(PPC) is an alternative fertilizer that can increase plant growth and production. The constituents of thenutrients can provide elements that are not present in the soil. This study aims to get the right dose forgrowth and production of corn (Zea mays L). The treatment consists of 7 levels O0 = N, P, KRecommended dosage (Urea = 5 g / array; TSP = 2.50 g / KCl array = 1.87 g / array) O1 = Standardorganic compost / fertilizer (gr / plot) ) + N, P, K (Urea = 5 g / bolt; TSP = 2.50 g / bolt; KCl = 1.87 g/ bolt) O2 = 0.75 ml Primatan + N, P, K (Urea = 5 g / run; TSP = 2.50 g / run; KCl = 1.87 g / run) P3= 1.12 ml Primate + N, P, K (Urea = 5 g / run; TSP = 2.50 g / extract; KCl = 1.87 g / extract) O4 =1.5 ml Primatan + N, P, K (Urea = 5 g / extract; TSP = 2.50 g / extract; KCl = 1.87 g / array) O5 =1.5 ml Primatan + 0.75 N, P, K (urea = 3.75 g / run; TSP = 1.87 g / run; KCl = 0.14 g / run) O6 = 1.5ml primatan + 0.50 N, P, K (urea = 2.50 g / bolt; TSP = 1.25 g / bolt; KCl = 0.93 g / bolt). TreatmentP2 = 0.75 ml Primatan + N, P, K (Urea = 5 g / line; TSP = 2.50 g / line; KCl = 1.87 g / line) is able togive the best results for all parameters, namely plant height amounting to 44.09 cm, leaf area 241.19mm3, biomass weight per plant sample 271.50 g, selling fresh weight 225.50 g, total chlorophyll30.93units / 6 mm3.